Cu2+-mediated fluorescence switching of gold nanoclusters for the selective detection of clioquinol. Issue 24 (16th November 2015) - Wang, Jian; Chang, Yong; Zhang, Pu; Lie, Shao Qing; Gao, Peng Fei; Huang, Cheng Zhi
Abstract : In this contribution, a rapid and selective fluorescence switchable strategy was developed for clioquinol by taking gold nanoclusters as probes and Cu 2+ as mediator, which is applicable to determination of clioquinol in cream with satisfactory results. Abstract : It is of great significance to sense clioquinol (CQ) in a simple and fast way because of its potential application in the treatment of neurodegenerative diseases. In this contribution, we proposed a Cu 2+ -mediated fluorescence switchable strategy to detect CQ by taking bovine serum albumin (BSA) protected gold nanoclusters (AuNCs) as probes. It was found that the strong red fluorescence of BSA-protected AuNCs at 610 nm could be effectively quenched by Cu 2+ (off state) and reversibly recovered by CQ (on state) owing to the specific coordination of CQ and Cu 2+ . Under the optimal conditions, there was a good linear relationship between the off–on efficiency ( E off–on ) and the amount of CQ in the range of 1–12 μM ( R 2 = 0.9902), with a detection limit of 0.63 μM (3 σ ). The "turn off–on" mode and the fast and unique complexation of CQ and Cu 2+ endow AuNCs with high specificity for CQ sensing. The proposed strategy is label-free, fast and selective, which is applicable to the analysis of CQ in cream with satisfactory results.